2005
DOI: 10.1002/ijc.21311
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid, a natural cytotoxic agent, fails to trigger apoptosis in human Burkitt's lymphoma‐derived B‐cell lines

Abstract: Betulinic acid (BA), a pentacyclic triterpene of natural origin, effectively induces apoptosis in neuroectodermal tumors and was recently shown to be a potent trigger of cell death in human leukemia-derived cell lines. To explore the potential of BA in the treatment of hematologic malignancies, we tested a panel of 10 Burkitt's lymphoma (BL)-derived B-cell lines for sensitivity to BA. The human Jurkat T leukemia cell line was included as a positive control. Our studies show that BA exerts cytotoxic effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…For flow cytometric assessment of DNA content and cell cycle distribution (Karpova et al, 2006), cells were harvested and resuspended in a solution containing PI (50 mg/ml), 0.1% Triton X-100, and 0.1% sodium citrate in PBS. Cells were then analyzed on a FACScan (Becton Dickinson) operating with CellQuest software (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…For flow cytometric assessment of DNA content and cell cycle distribution (Karpova et al, 2006), cells were harvested and resuspended in a solution containing PI (50 mg/ml), 0.1% Triton X-100, and 0.1% sodium citrate in PBS. Cells were then analyzed on a FACScan (Becton Dickinson) operating with CellQuest software (Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, their beneficial effects have been analysed by extensive preclinical and epidemiological studies [1][2][3][4]. Some natural triterpenoids such as oleanolic, betulinic and ursolic acids have shown notable effects in suppressing tumourigenesis as well as inhibiting tumours [1,[5][6][7][8][9]. Also, a range of newly developed synthetic triterpenoids are more potent than the naturally occurring parent structure [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, cells were harvested, washed and resuspended in a HEPES buffer containing annexin V-FITC and propidium iodide (PI) (100 mg/ml) before analysis on a FACScan (Becton Dickinson), as described previously. 10 Cellular uptake of FITC-conjugated Smac and control peptides (see section above) was also assessed using a FACScan operating with CellQuest software (Becton Dickinson).…”
Section: Flow Cytometric Determination Of Apoptosismentioning
confidence: 99%
“…To verify that the importance of Apaf-1 for apoptosis signaling is not limited to the Raji cell line, we utilized DG-75-lymphoma cells, that are resistant to the chemotherapeutic agent, etoposide, 10,11 as well as to STS (the present study). Our previous studies have shown that the lipid raft-disrupting agent, methylb-cyclodextrin (MCD), can sensitize both the Raji cell line and the DG-75 cell line to cytochrome c-dependent activation of caspases, through the liberation of endogenous Apaf-1 from the plasma membrane.…”
Section: Lipid Raft Disruption Enables Smac-mediated Potentiation Of mentioning
confidence: 99%
See 1 more Smart Citation